Faith in the Halls of Power: How Evangelicals Joined the American Elite - Olson, Laura R. (Sociology of religion, 2010)
It is not often in academia that we can honestly describe a book as an engaging read, but D. Michael Lindsay's Faith in the Halls of Power is a deeply engaging—and genuinely interesting—book. Its greatest strength lies in its tremendous practical relevance to understanding life in the contemporary United States. The most significant story of religion in late twentieth- and early twenty-first-century America undoubtedly has been evangelical Protestantism's rise to social prominence and, correspondingly, to political and economic power. Lindsay's book explores this societal transformation in compelling, personalized detail.